High-Temperature Mechanical Properties and Microstructure of High Belite Cement - Zhiqiang, Wu; Renjun, Xie; Jin, Yang; Xiucheng, Ni; Xiaowei, Cheng (Frontiers in Materials, 2022)
The use of the G-class oil well cement for cementing in high-temperature deep-seated oil and gas wells declines its mechanical properties, and it exhibits high-temperature brittleness and low tensile stress, which limit its application under high-temperature conditions. The high belite cement (HBC), a new class of energy-saving and environmentally friendly cement, has been widely used in recent years. In this study, the mechanical properties, phase composition and microstructure of HBC and quartz sand have been analyzed at high temperature, so as to optimize the amount of sand and provide guidelines for further exploring the application of HBC in the high-temperature oil and gas well cementing. The experimental results show that the high-temperature mechanical properties of the cement stone mixed with 40% quartz sand are the highest, thus, delaying the decline in the strength to the greatest extent. The microscopic analysis reveals that HBC produces dicalcium silicate hydrate and hydroxyl silicon calcium stone at high temperature. On mixing the quartz sand, xonotlite is observed to appear in the cement hydrate phase. These products are observed to be small in size and dense in structure, thus, leading to a delay in the decline of the high-temperature mechanical properties of the cement stone.